2010
DOI: 10.1111/j.1365-2486.2009.02095.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting spatial and temporal patterns of bud‐burst and spring frost risk in north‐west Europe: the implications of local adaptation to climate

Abstract: The timing of spring bud-burst and leaf development in temperate, boreal and Arctic trees and shrubs fluctuates from year to year, depending on meteorological conditions. Over several generations, the sensitivity of bud-burst to meteorological conditions is subject to selection pressure. The timing of spring bud-burst is considered to be under opposing evolutionary pressures; earlier bud-burst increases the available growing season (capacity adaptation) but later bud-burst decreases the risk of frost damage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 63 publications
2
92
1
2
Order By: Relevance
“…According to field observations, the heat sum requirement for bud break of birch decreases from south to north in the boreal region [94,95] and also the temperature threshold for the NDVI-based greening-up decreases [28,77]. This seems to be in contradiction to our results for JSBACH DBF_SOS mod .…”
Section: Modelling Of Springtime Development and The Start Of Seasoncontrasting
confidence: 56%
“…According to field observations, the heat sum requirement for bud break of birch decreases from south to north in the boreal region [94,95] and also the temperature threshold for the NDVI-based greening-up decreases [28,77]. This seems to be in contradiction to our results for JSBACH DBF_SOS mod .…”
Section: Modelling Of Springtime Development and The Start Of Seasoncontrasting
confidence: 56%
“…After the TP of spring NDVI, both browning and cooling are observed, particularly in the above-mentioned regions. Such negative effects of spring cooling on vegetation growth of northern ecosystems may be not only associated with the delayed vegetation greening (21-23) but also related to the increasing risk of spring frost or extreme low temperature (24)(25)(26). It has been suggested that spring frost may severely damage vegetation growth, particularly when it took place after budburst (24).…”
Section: Resultsmentioning
confidence: 99%
“…In fact the regulation of the timing of growth onset and cessation is a fundamental feature allowing the syncronisation of the plant growth cycle with favourable seasonal conditions, and, similar to other characteristics, has been driven by selective pressure (Leopold 1996;Bennie et al 2010;Korner and Basler 2010). This process of adaptation has been seen as the result of stabilising selection caused by two opposite forces: protection against an unfavourable season (survival adaptation), and effective use of growing resources (capacity adaptation) (Hänninen and Hari 1996;Leinonen and Hänninen 2002).…”
Section: Introductionmentioning
confidence: 99%